Middleware para Aplicações Distribuídas de Vídeo com Suporte à Computação na Borda na Indústria 4.0 - Ramos Neto, Otacílio de A.; Chaves, Rafael C.; Nascimento, Alysson P.; Gomes, Ruan D. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2024.242927, 2024)
Within the scope of Industry 4.0, computer vision is extensively employed for monitoring and control functions with stringent demands on performance and latency. A viable approach to meeting these requirements is distributed processing at the edge and in the cloud. In this context, this paper presents a middleware tailored for Industry 4.0 and distributed video applications using edge computing. A versatile communication protocol was developed, with support to both UDP and TCP, and incorporating two methods for frame delivery prioritization (either Last In, First Out or First In, First Out). Also, the protocol performs fragmentation, enabling the transmission of high-resolution images. Initial experiments have shown that the proposed middleware allows the distribution of high-resolution videos without significant overhead, while at the same time offering a high level of transparency for applications, which can be implemented as if getting the video stream from a locally connected camera.